KESIAPAN INTEGRASI LAYANAN TB-HIV PUSKESMAS DI KABUPATEN KULON PROGO - Titi Supriati; Yodi Mahendrahata; Ari Natalia Probandari (Journal of Health Service Management, 2021)
Background: Indonesia is one of the countries with a high burden of TB and HIV. In response, countries adopted collaborative TB-HIVguidelines which recommending integrated services including diagnostic screening and care for TB-HIV patients. In Kulon Progo, onlyhalf of the target achieved for HIV testing on TB patients and efforts to improve services under the existing health system resources.Therefore, it is very important to understand its capacity to provide integrated TB-HIV services.Objective: This study aimed to assess the readiness for integration of TB-HIV services at the Puskesmas for the health system in Kulon Progo District.Methods: The research used mixed methods explanatory sequential design. The unit of analysis was the Puskesmas. Crosssectional observations using a modified SARA questionnaire followed by in-depth interviews explored the barriers and opportunitiesfor integration of TB-HIV services at the Puskesmas were conducted.Results: Overall from 21 Puskesmas, 93.3% (95% CI; 92.7%-93.9) Puskesmas had readiness to provide basic health services, 63.8%(95% CI, 60.7–66.8) Puskesmas had TB service readiness, 80.9% (95% CI: 73.6–88.2) Puskesmas had readiness for HIV testing counseling services, only 1 Puskesmas (4.7%) had good readiness forboth services. Based on the domain assessment, only 40.4% of Puskesmas have trained staff in TB diagnosis and treatment and61.9% of Puskesmas have trained personnel and guidance on HIV testing counseling. Leadership involvement had a positive effecton strengthening integration readiness, while negative responses from access to knowledge and training weaken service integration readiness.Conclusion: Puskesmas had good readiness for general services and HIV counseling services. However, readiness for TB serviceswas suboptimal, only one puskesmas had readiness in the good category for both services. Leadership involvement coordinatesthe two services and directs management support to strengthen integration readiness. Trained staff and the availability of TB-HIV guidelines must be met to support the integration of TB-HIV services.